2017
DOI: 10.1021/acsinfecdis.7b00090
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide and Reactive Sulfur Species Impact Proteome S-Sulfhydration and Global Virulence Regulation in Staphylococcus aureus

Abstract: Hydrogen sulfide (H2S) is thought to protect bacteria from oxidative stress, but a comprehensive understanding of its function in bacteria is largely unexplored. In this study, we show that the human pathogen Staphylococcus aureus (S. aureus) harbors significant effector molecules of H2S signaling, reactive sulfur species (RSS), as low molecular weight persulfides of bacillithiol, coenzyme A, and cysteine, and significant inorganic polysulfide species. We find that proteome S- sulfhydration, a post-translation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
149
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(163 citation statements)
references
References 68 publications
11
149
3
Order By: Relevance
“…Although we found that H 2 S does not affect H. pylori growth, it has been described that H 2 S can signal in bacteria such as Staphylococcus aureus through S-sulfhydration (16). This mechanism, which can be potentiated by the gasotransmitter NO, results in the regulation of protein activities, an increase of the antioxidant capacity, and virulence gene expression (16,46). Consequently, the effect of macrophage CTH-derived H 2 S on H. pylori gene expression deserves further investigation.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Although we found that H 2 S does not affect H. pylori growth, it has been described that H 2 S can signal in bacteria such as Staphylococcus aureus through S-sulfhydration (16). This mechanism, which can be potentiated by the gasotransmitter NO, results in the regulation of protein activities, an increase of the antioxidant capacity, and virulence gene expression (16,46). Consequently, the effect of macrophage CTH-derived H 2 S on H. pylori gene expression deserves further investigation.…”
Section: Discussioncontrasting
confidence: 81%
“…Epithelial and immune cells of the gastrointestinal tract can produce hydrogen sulfide (H 2 S), the third gaseous signaling molecule associated with physiological properties (11), including vasorelaxation (12), neuroprotection (13), oxidant regulation (14), and anti-inflammatory action (15). In addition, H 2 S has been shown to signal in pathogenic bacteria (16). H 2 S is synthesized in biological milieus by three enzymes, namely, cystathionine ␀-synthase (CBS), cystathionine ␄-lyase (CTH), and mercaptopyruvate sulfurtransferase (MPST).…”
mentioning
confidence: 99%
“…Several key host transcription factors, Nrf2 and Nf‐ÎșB, are directly targeted by H 2 S via S‐persulfidation . Apart from eukaryotic systems, a recent study, for the first time, assessed widespread S‐persulfidation of proteins in Staphylococcus aureus ( S. aureus ) . More importantly, H 2 S exposure increased the level of S‐persulfidation, whereas mutations in transsulfuration pathways ( cysM and metB ) had an opposite effect .…”
Section: Chemical Biology Of H2smentioning
confidence: 99%
“…A reasonable hypothesis is that they use glutathione (GSH) or NADPH to reduce sulfane sulfur to H 2 S and then release it out of cells (Carbonero et al, 2012) , as observed in anaerobically cultured fungi (Abe et al, 2007; Sato et al, 2011) . A recent report that two thioredoxin-like proteins catalyze the reduction of protein persulfidation in Staphylococcus aureus also support the hypothesis (Peng et al, 2017) . However, it is unclear whether sulfane sulfur induces the expression of these enzymes.…”
Section: Introductionmentioning
confidence: 58%
“…As nucleophiles, they are better reductants than thiols (Ida et al, 2014) ; as electrophiles, the electrophilic sulfane sulfur (S 0 ) can be transferred to protein thiols to generate protein-SSH, which modifies enzyme activities and protects proteins from irreversible oxidation (Mustafa et al, 2009; Paul & Snyder, 2015) . Owing to these unique dual-reactivities, reactive sulfane sulfur is involved in many cellular processes, such as redox homeostasis maintenance, virulence regulation in pathogenic bacteria, and biogenesis of mitochondria (Fujii et al, 2018; Peng et al, 2017) . Albeit the good roles, sulfane sulfur may be toxic at high concentrations.…”
Section: Introductionmentioning
confidence: 99%